Project Management-BITP3223, BITs3323, BITM3113 - Zakaria, Mohd Hafiz; Ahmad, S.; Yusof, R.; Salam, S. (Jawatankuasa Penerbitan FTMK, 2006)
The objectives of this module is to introduce students with software for project management using the top project management software tool in the industry namely Microsoft project.This software will help students in understanding and applying the project management knowledge areas and processes. We will also use other tools such as spreadsheet software, which is Microsoft Excel and Internet Browsers. Each lab offers students many opportunities to get hands-on and build new software skill.